Empatía, antropomorfismo y cognición animal - Scotto, Silvia Carolina (2015)
In this paper I argue that attributions of certain cognitive abilities to some animal species, based on inter-species empathy, are supported on a presupposition according to which those animal species are minded creatures. This implicit premise gives support to a "transcendental" argument, based on empathy, in favor of animal cognition, that justifies the anthropomorphic character of ordinary psychological attributions. Furthermore, abundant empirical grounds and theoretical hypothesis explain the nature and the adaptive functions of empathy and anthropomorphism, shaping a complementary "cognitive-evolutive" argument. The two faces of this "empathic argument", the trascendental and the empirical one, strengthen the idea of a line of relative continuity between our ordinary point of view about us and our ordinary point of view about some animal species, that is founded on the existence of a line of continuity between species, and therefore, on an evolutionary explanation of these socio-cognitive basic abilities.